Behavioral approaches to brain research - Robinson, Terry E. (Oxford University Press, 1983)
y study behavior in brain research?: The influence of psychological concepts on brain-behavior research / C.H. Vanderwolf. Why measure behavior? / S.J. Hutt and Corinne Hutt. Neurology and the mind-brain problem / R.W. Sperry -- Behavioral approaches to brain research: Vision as a sensorimotor system / M.A. Goodale. Single neuron recording in behaving mammals--bridging the gap between neuronal events and sensory-behavioral variables / James B. Ranck, Jr. ... [et al.] A behavioral approach to the analysis of reticular formation unit activity / Jerome M. Siegel. Behavioral insights into neural changes accompanying visual development and deprivation / Douglas C. Smith. The analysis of behavior in the laboratory rat / Ian Q. Whishaw, Bryan Kolb, and Robert J. Sutherland. The conditioned defensive burying paradigm and behavioral neuroscience / John P.J. Pinel and Dallas Treit -- Generalizing in brain-behavior research: Problems and principles underlying interspecies comparisons / Bryan Kolb and Ian Q. Whishaw